Impact of 6-Month Exercise Program on Weight Status and Associated Biomarkers in Mild Cognitive Impairment. (12th July 2011) - Spitznagel, Mary Beth; Miller, Lindsay A.; Potter, Vanessa; Glickman, Ellen; Gunstad, John
Abstract : Unintentional weight loss in Alzheimer's disease (AD) predicts morbidity and mortality, but effectiveness of dietary supplementation is reduced in those with low body mass index. Exercise may be beneficial, particularly if started early. Thirty-one participants with mild cognitive impairment (MCI) completed measures of cardiovascular fitness, eating behavior, cognitive function, and body composition before and following a 6-month exercise program. Ghrelin, leptin, and brain-derived neurotrophic factor were measured to elucidate the relationship between cognition and response to exercise. Significant baseline relationships emerged among appetite and both cardiovascular fitness and neurocognition. Following the exercise program, improvements in cardiovascular fitness and healthy eating habits occurred, body composition and biomarkers remained stable, and cognition declined. This study suggests exercise may benefit persons with MCI by promoting healthier eating habits and possibly stabilizing body composition and biomarkers. Although increased fitness did not stabilize cognitive decline in MCI, exercise may positively impact eating behavior.